1980
DOI: 10.1111/j.1365-2265.1980.tb02714.x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Function Tests in Sheehan's Syndrome

Abstract: Fourteen patients with a typical history of Sheehan's syndrome underwent pituitary function tests with simultaneous injections of 100 micrograms LH-RH, 200 micrograms TRH and 0.05--0.1 units of soluble insulin per kg body weight. Serum prolactin levels remained unchanged in all of eleven subjects given TRH. GH levels did not rise after hypoglycaemia in five subjects. In contrast serum LH and FSH rose significantly in twelve out of fourteen subjects given LHRH and serum TSH rose significantly in five out of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
3

Year Published

1983
1983
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 23 publications
(15 reference statements)
1
22
0
3
Order By: Relevance
“…However, there are contradictory reports about PRL deficiency in SS. Many studies have reported that PRL deficiency was sine qua non for the diagnosis of SS (7,30,32,33). On the other hand, Ramiandrasoa et al (8) reported that ten out of 24 (42%) patients with SS did not have lactotroph insufficiency, defined by a basal PRL level below 3 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are contradictory reports about PRL deficiency in SS. Many studies have reported that PRL deficiency was sine qua non for the diagnosis of SS (7,30,32,33). On the other hand, Ramiandrasoa et al (8) reported that ten out of 24 (42%) patients with SS did not have lactotroph insufficiency, defined by a basal PRL level below 3 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…The most consistent finding in SS is the loss of somatotroph and thyrotroph function; though the loss of somatotroph function is universal, there are varying reports about involvement of thyrotroph function. Several previous series reported thyrotroph failure in 90% of patients (6,8,9,13) and one reported it in all the patients (8). All of our patients had thyrotrophs failure.…”
Section: Discussionmentioning
confidence: 63%
“…Low levels of cortisol and gro wth hormone also contribute to increase in TSH release in these patients. The increased TSH produced has low intrinsic bioactivity and decreased metabolic clearance (11,12 tuitary gland and are damaged predominantly during the ischemic necrosis (13). There is a consensus among different series that GH deficiency is a universal finding in SS (2,7 9,14).…”
Section: Discussionmentioning
confidence: 99%
“…A extensão da disfunção hipofisária varia nas diversas séries (10,(17)(18)(19)(20)(21)(22), visto que na maioria dos estudos o principal acometimento foi o da secreção de prolactina e GH (90% a 100%), enquanto as deficiências na secreção de cortisol, TSH e gonadotrofinas variaram de 50% a 100%. A deficiência de GH é muito comum na síndrome de Sheehan, desde que os somatotrófos estejam localizados nas regiões inferiores e laterais da hipó-fise, sendo bastante suscetíveis à isquemia (23).…”
Section: Aspectos Clínicos E Laboratoriaisunclassified
“…Apesar de a agalactia ser o sinal clínico mais comum observado nas pacientes com síndrome de Sheehan, e alguns autores sugerirem que a ausência de resposta da prolactina à administração de TRH (hormônio liberador de tireotrofina) seja um procedimento confiável e sensível para o screening de pacientes suspeitas de síndrome de Sheehan (19)(20)(21), há relatos de pacientes com a síndrome que apresentam galactorréia e hiperprolactinemia (24,25). Embora a referência de amenorréia após o parto seja também freqüente, em muitas séries a função gonadotrófica estava preservada e há vários relatos de pacientes com síndrome de Sheehan que mantiveram ciclos menstruais regulares e até engravidaram de maneira espontânea (26)(27)(28)(29)(30)(31)(32).…”
Section: Aspectos Clínicos E Laboratoriaisunclassified